Adsorption of Some Pharmaceutical Drugs (Metformin, Aspirin and Ponstan) and Their Assessment from Aqueous Solution - Ali, Karar Hadi Abboud; Hasson, Zainab Saleem Abdulrasool; Fayyad, Aya Laith Farhan; khalaf, Ahmed omer ismail; Abed, Hajer Khalid Mohammed (American Journal of Biomedicine and Pharmacy, 2024)
Metformin, aspirin and ponstan are pharmaceutical drugs used in human and veterinary medicine that is readily transported into the environment via domestic wastewaters and through direct run off. The event of over dose will cause poisoning and kidney pains and muscle ache. Adsorption of Metformin, aspirin and ponstan from aqueous solutions has been studied in this work two adsorption isotherms equations were employed including Freundlich and Langmuir equations. The adsorption was assessed using different isotherms and kinetic models. Then, researchers explained some applications of adsorption from aqueous solutions.